Constructed Identities and Potent Imaginaries: A Missiological Reflection on Mainland Chinese Ethnic and Racial Identity in a Divided and Broken World - Ng, David H. F. (Mission studies, 2022)
This paper offers a missiological reflection on the construction of Mainland Chinese ethnic and racial identity. Through a survey of scholarly literature on both the ethnic classification project in Mainland China and “yellow” as a racial designator in Western imagination, this article demonstrates their fluid, constructed, and imagined nature in the context of power, inequality, and vulnerability. While these imposed constructions are contested and negotiated, they are also, to varying extents, shared and accepted. This article also argues that such constructed identities and imaginaries can powerfully shape our understanding and encounter with others in our increasingly diverse and interconnected world. For the Christian, Jesus’ humble, self-giving, sacrificial love and service should shape our identity and relationship with others in ways that transcend our inherited ethnic and racial identity constructions. As citizens of heaven, Christians – in both their attitudes and practices – should thus model an alternative to the ethnic and racial division and brokenness already evident in the church and the world.